Postinfectious glomerulonephritis: Is there a link to alcoholism? - Keller, Christine K.; Andrassy, Konrad; Waldherr, Rüdiger; Ritz, Eberhard (QJM, 1994)
From January 1984 to May 1993, we observed 30 cases of postinfectious glomerulonephritis (GN)- endocapillary, exudative GN with humps (23 males, 7 females; median age 49 years; range 17-77). They represented 4.5% of all renal biopsies. Crescents were present in 9/26 who had renal biopsies (35%) and there was a mesangioproliferative pattern in 14 (54%). Seventeen of the 30 patients (57%) were alcoholics by history and biochemistry. Cirrhosis was present in 8/17 (47%), but alcoholic hepatitis in none. Nine of the 17 alcoholic (53%) but none of the non-alcoholic patients developed chronic renal failure. Adverse renal prognosis was significantly correlated to alcoholism. We conclude that (i) alcoholism is common in patients with postinfectious GN, and, (ii) alcoholism adversely affects renal prognosis in patients with postinfectious GN.